1990
DOI: 10.1128/iai.58.6.1821-1827.1990
|View full text |Cite
|
Sign up to set email alerts
|

Disparate mechanisms of induction of procoagulant activity by live and inactivated bacteria and viruses

Abstract: This study describes the dose response, time course, and lymphocyte requirements of procoagulant activity (PCA) induction following stimulation of thioglycolate-elicited BALB/c peritoneal macrophages with live and inactivated bacteria (Bacteroides fragiis, Escherichia coli, and Staphylococcus aureus) and murine hepatitis virus type 3 (MHV-3). Induction of PCA by MHV-3 was significantly more rapid and the maximal PCA achieved was significantly greater than by the three bacterial species studied. In relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Increased vascular permeability may expose contact factors of plasma to activators, such as collagen, in the extravascular space. In addition, cells of monocyte-macrophage lineage are known to express PCA on their cell surface in response to a variety of inflammatory stimuli, including endotoxin (24), immune complexes (34), and proteolytic products of the complement cascade (28), as well as several microbial pathogens (12,35,39,43).…”
Section: Discussionmentioning
confidence: 99%
“…Increased vascular permeability may expose contact factors of plasma to activators, such as collagen, in the extravascular space. In addition, cells of monocyte-macrophage lineage are known to express PCA on their cell surface in response to a variety of inflammatory stimuli, including endotoxin (24), immune complexes (34), and proteolytic products of the complement cascade (28), as well as several microbial pathogens (12,35,39,43).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was used over the range of 1 to 10,000 mU of PCA, with this range being linear with normal plasma substrate. Previous studies have shown that PCA induced by bacteria and endotoxin are tissue factor-like activities, making comparison with a thromboplastin standard appropriate (13,14).…”
mentioning
confidence: 99%
“…The pathogenesis of the fibrin‐ring is not well established, but in vitro studies have shown that histiocytes stimulated by infection produce a procoagulant activity substance leading to the formation of long needles of fibrin on the surface of monocytes and macrophages 29,30 . The evolutionary sequence of the different granulomatous patterns remains speculative but Travis 21 noticed in bone marrow biopsies that doughnut granulomas persisted in untreated patients, until at least two month after the onset of the symptoms, even after other types of granulomas were no longer present.…”
Section: Discussionmentioning
confidence: 99%